Mechanistic Drivers of Müllerian Duct Development and Differentiation Into the Oviduct - Santana Gonzalez, Laura; Rota, Ioanna A.; Artibani, Mara; Morotti, Matteo; Hu, Zhiyuan; Wietek, Nina; Alsaadi, Abdulkhaliq; Albukhari, Ashwag; Sauka-Spengler, Tatjana; Ahmed, Ahmed A. (Frontiers in Cell and Developmental Biology, 2021)
The conduits of life; the animal oviducts and human fallopian tubes are of paramount importance for reproduction in amniotes. They connect the ovary with the uterus and are essential for fertility. They provide the appropriate environment for gamete maintenance, fertilization and preimplantation embryonic development. However, serious pathologies, such as ectopic pregnancy, malignancy and severe infections, occur in the oviducts. They can have drastic effects on fertility, and some are life-threatening. Despite the crucial importance of the oviducts in life, relatively little is known about the molecular drivers underpinning the embryonic development of their precursor structures, the Müllerian ducts, and their successive differentiation and maturation. The Müllerian ducts are simple rudimentary tubes comprised of an epithelial lumen surrounded by a mesenchymal layer. They differentiate into most of the adult female reproductive tract (FRT). The earliest sign of Müllerian duct formation is the thickening of the anterior mesonephric coelomic epithelium to form a placode of two distinct progenitor cells. It is proposed that one subset of progenitor cells undergoes partial epithelial-mesenchymal transition (pEMT), differentiating into immature Müllerian luminal cells, and another subset undergoes complete EMT to become Müllerian mesenchymal cells. These cells invaginate and proliferate forming the Müllerian ducts. Subsequently, pEMT would be reversed to generate differentiated epithelial cells lining the fully formed Müllerian lumen. The anterior Müllerian epithelial cells further specialize into the oviduct epithelial subtypes. This review highlights the key established molecular and genetic determinants of the processes involved in Müllerian duct development and the differentiation of its upper segment into oviducts. Furthermore, an extensive genome-wide survey of mouse knockout lines displaying Müllerian or oviduct phenotypes was undertaken. In addition to widely established genetic determinants of Müllerian duct development, our search has identified surprising associations between loss-of-function of several genes and high-penetrance abnormalities in the Müllerian duct and/or oviducts. Remarkably, these associations have not been investigated in any detail. Finally, we discuss future directions for research on Müllerian duct development and oviducts.